Performance analysis of the real time kinematic GPS (RTK GPS) technique in a highway project (stake-out) - Pirti, A. (TAYLOR & FRANCIS LTD, 2007)
RTK GPS has seen great technological advances over the past few years and is now routinely used in a wide variety of engineering type applications. RTK GPS provides centimetre level position in seconds, allowing workers to get the precision. One GPS receiver is placed in a control point (named the reference station) with known coordinates. RTK system combine GPS information and data radio communication with advanced algorithms to calculate precise position of the projects, such as highway and bridge, GIS project. The RTK GPS technology has been integrated into surveying activities such as construction stakeout, topography, and as-built surveys. Accuracy has been increased and productivity has doubled by using RTK GPS technique. Projects are executed in a timelier manner and the manpower savings is actually paying for the equipment investment. This study investigates the RTK achievable accuracy and repeatability under different satellite configurations and site conditions in highway stake-out project. Results show that the RTK is more stable for horizontal coordinates than the height, and data latency generates errors of a few millimetres. Positioning accuracy on the cm level can be routinely achieved when observing sufficient number of satellites. To evaluate performance of the RTK method four tests were carried out in the highway project (stakeout). The objectives of the tests were to assess the RTK achievable accuracy and check the repeatability of the results under different satellite configurations. The tests were to evaluate RTK performance near the forest and in an urban environment under varying site conditions, and expected problems due to signal blockage and data latency.
Keywords: RTK GPS; performance; accuracy; repeatability; highway example; AMBIGUITY DECORRELATION ADJUSTMENT; Engineering; Geology; Remote Sensing